Implementation of Inclusive Education at Elementary School 4 Kasongan Lama - Dora Dora (International Journal of Universal Education, 2026)
Inclusive schools are educational services provided to children with special needs to ensure they receive an appropriate education. Government policies, as stipulated in Law Number 20 of 2003, Article 32, and the Minister of National Education Regulation Number 70 of 2009, provide opportunities for children with special needs to receive education in regular schools. In inclusive schools, children with special needs can learn alongside typically developing children and are treated the same as other children. This demonstrates the positive psychological impact of inclusive schools on children with special needs. Various problems that have emerged after more than ten years of implementation in inclusive education practice indicate challenges hindering its implementation in Indonesia. One of these factors is teacher competence, as teachers are not yet fully able to handle children with special needs in regular classrooms. The success of implementing inclusive schools depends on teachers' competence and on collaboration among schools, the government, and parents.